Craniometrical imaging and clinical findings of adult Chiari malformation type 1 before and after posterior fossa decompression surgery with duraplasty. (3rd September 2019) - Nikoobakht, Mehdi; Shojaei, Hamidreza; Gerszten, Peter C.; Shojaei, Seyedeh Fahimeh; Mollahoseini, Reza; Azar, Maziar
Abstract: Background: Posterior fossa decompression both with and without duraplasty are accepted treatments for symptomatic adult patients with Chiari Malformations Type 1 (CM-1). There is still debate of the superiority of one technique over the other. The purpose of this study was to determine the clinical and craniometrical imaging outcomes of a series of patients who underwent posterior fossa decompression with duraplasty. Materials and methods: All adult patients with symptomatic CM-1 operated at a single institution with a minimum of 6 months follow-up were enrolled prospectively. Clinical outcomes and craniometrical parameters based upon MR imaging pre- and post-surgery were analyzed. Results: A series of 33 consecutive patients who met the inclusion criteria were enrolled; mean age of 33.93 ± 10 years (range 14–56 years). The most common preoperative complaint was headache. The most common clinical sign was sensory dysfunction which was relieved or improved in 63% of patients. The mean syringomyelia size had a significant reduction after the surgery ( p  = .01). The mean tonsillar descent also had significant reduction ( p  = .00). The mean McRae line length before the surgery and after that were 33.4 and 53.1 mm respectively that this change was not statistically significant ( p  = .42). The odontoid process parameters had no significant changes after surgery. Conclusions: Posterior fossa decompression surgery with duraplasty can improve both clinical and imaging outcomes such as syringomyelia size and tonsillar descent for patients with symptomatic CM-1. However, no significant difference was found in craniometrical parameters before and after the surgery.